Implementasi Konsep Arsitektur Ramah Lingkungan pada Pusat Kecantikan di Makassar - Pratiwi, Armila; Rahayu, Irma; Sam, Mukhlishah (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
The design of a beauty center in Makassar faces challenges in meeting both user comfort and aesthetic needs while maintaining environmental sustainability. This study aims to apply ecological architecture principles to the design of the beauty center, creating a building that is environmentally friendly, energy-efficient, and supportive of user well-being. The research employed literature review, precedent analysis, and field surveys to gather data on the site, environmental conditions, and similar buildings. The design results indicate that applying ecological architecture principles—such as strategic vegetation placement, extensive green open spaces, use of environmentally friendly materials, and natural lighting and ventilation—creates a comfortable, cool, and aesthetically pleasing environment. Integrating these eco-friendly principles into the site, exterior, and interior enhances air quality and energy efficiency and provides a safe and calming space for visitors. Therefore, the application of ecological architecture strengthens the aesthetic and functional performance of the beauty center while maintaining the local ecosystem balance and supporting holistic environmental sustainability.